The Concept of Treatment of Scolioses Employing Asymmetrical Aquatic Exercises - Wioletta Łubkowska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
According to the statistical data, there is being observed a definite increase in percentage of children affected by posture defects, particularly scolioses. The aquatic environment facilitates treatment of scolioses, since it provides relief conditions used in order to perform prophylactic, corrective and therapeutic tasks. Hydrokinetic therapy is one of the many rehabilitation methods. It seems, however, that corrective and therapeutic swimming is far too rarely used as an auxiliary measure for treatment of scolioses. This paper presents the concept of treatment of scolioses employing asymmetrical exercises in aquatic environment, the author of which in Poland is Iwanowski. In the study desk research of literature studies was applied along with the analysis of publications, including available study reports, articles, documents and also own video and photographic materials. The author suggests the concept of conservative treatment of scolioses through the application of asymmetrical swimming exercises in aquatic environment. Such procedure is efficient in preventing significant spinal deformations, which may protect against surgical intervention.